PENGARUH PRICE EARNING RATIO, PRICE TO BOOK VALUE, INFLASI, DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM (Studi Kasus Pada Perusahaan Sub Sektor Transportasi yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022) - Nindya, Nindya Eka Putri Pangestu; Lasmana, Andy; Aziz, Ayi Jamaludin (Komunitas Manajemen Kompetitif, 2024)
This research aims to determine the effect of price earning ratio, price to book value, inflation, debt to equity ratio on share prices in transportation sub-sector companies listed on the Indonesian Stock Exchange in 2018-2022. This research uses quantitative methods using time series data. The data used is secondary data with data analysis techniques using calculations based on JASP assistance which is aimed at testing predetermined hypotheses. The research results show that the Price Earning Ratio variable has a significant effect on stock prices, while price to book value, inflation and debt to equity ratio have no effect on stock prices. Keywords: Price Earning Ratio, Price To Book Value, Inflation, Debt To Equity Ratio, Stock Price